Lexical Fields of War in the Summary of Geneva Convention: Semantic Analysis - Muhammad Nabhan Hanif; Cipto Wardoyo; Ika Yatmikasari (Mauriduna : Journal of Islamic Studies, 2025)
This study explores the semantic structure of war-related language in the Summary of the Geneva Conventions of 1949 and Their Additional Protocols, emphasizing the importance of understanding how international humanitarian values are embedded in legal discourse. This study aims to identify the lexical fields associated with war and analyze how these fields reflect the Geneva Conventions’ core principles protection, legality, and humanitarianism. Using a descriptive qualitative method combined with document analysis and grounded in lexical field theory, this study categorizes 50 war-related terms into seven thematic fields: protection of individuals, legal and compliance terms, humanitarian actions, conflict and warfare, symbols and emblems, rights and protection, and specific protection. The findings show that each lexical group encapsulates distinct humanitarian and legal imperatives, illustrating how language functions as a normative force in international law. The novelty of this study lies in its application of semantic analysis to a foundational legal text, providing new linguistic insights into the codification of war ethics. This research not only contributes to semantic and legal linguistics but also holds policy implications by reinforcing the necessity for precise and human-centered language in legal instruments to enhance compliance and protection in armed conflict. Future policymaking could benefit from linguistic scrutiny of international law texts to ensure clarity, empathy, and enforceability in humanitarian protections.